2017
DOI: 10.1371/journal.pone.0176847
|View full text |Cite
|
Sign up to set email alerts
|

Ketoanalogues supplementation decreases dialysis and mortality risk in patients with anemic advanced chronic kidney disease

Abstract: BackgroundThe benefit of alpha-Ketoanalogues (KA) supplementation for chronic kidney disease (CKD) patients that followed low-protein diet (LPD) remains undetermined.MethodsWe extracted longitudinal data for all CKD patients in the Taiwan National Health Insurance from January 1, 2000 through December 31, 2010. A total of 1483 patients with anemic advanced CKD treated with LPD, who started KA supplementation, were enrolled in this study. We analyzed the risks of end stage renal disease and all-cause mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
4
25
1
2
Order By: Relevance
“…Much evidence has been reported showing that LPDs and vLPDs supplemented with ketoanalogues can help retard CKD progression [ 16 , 20 ] and postpone dialysis [ 23 , 39 ], including one study [ 40 ] that utilized the same database as the current research. However, the evidence of a possible long-term survival benefit of this diet therapy is limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence has been reported showing that LPDs and vLPDs supplemented with ketoanalogues can help retard CKD progression [ 16 , 20 ] and postpone dialysis [ 23 , 39 ], including one study [ 40 ] that utilized the same database as the current research. However, the evidence of a possible long-term survival benefit of this diet therapy is limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the benefits of ketoanalogues (KA) supplementation on mortality and renal outcomes in CKD patients undergoing dietary protein restriction are controversial [7][8][9][10][11]. First, regarding the effects of KA supplementation through a VLPD on patients with stage 4 and 5 CKD, Garneata et al conducted a prospective randomized controlled trial in 207 patients with estimated glomerular filtration rate (eGFR) < 30 mL/min and noted that KA supplementation with a vegetarian VLPD (0.3 g/kg body weight/day) could defer dialysis initiation compared with an LPD (0.6 g/kg body weight/day) alone [7].…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, both sVLPDs (0.3-0.4 g/kg body weight per day) [6] and low-protein diets supplemented with ketoanalogues (sLPDs) (0.6 g/kg body weight per day) [7] can dampen the consequences of protein metabolism, such as the accumulation of nitrogen waste products, metabolic acidosis, and hyperphosphatemia, while maintaining the protein-energy balance. Indeed, several randomized controlled trials (RCTs) [8,9] and observational studies [10,11] have proved that sVLPDs and sLPDs can delay the initiation of dialysis and slightly retard the decline of renal function. Moreover, in those who can adhere to the treatment and frequent follow-up of nutritional status, dietary therapy has been shown not to result in adverse effects during treatment [12,13] or after dialysis initiation [10,14].…”
Section: Introductionmentioning
confidence: 99%